Self-assembled c-axis oriented antiperovskite soft-magnetic CuNCo3 thin films by chemical solution deposition1. Issue 17 (7th May 2015) - Hui, Zhenzhen; Tang, Xianwu; Shao, Dingfu; Wei, Renhuai; Yang, Jie; Tong, Peng; Song, Wenhai; Zhu, Xuebin; Sun, Yuping
<x xml:space="preserve">Abstract</x> Self-assembled c-axis oriented ternary antiperovskite soft-magnetic CuNCo3 thin films with a Curie temperature higher than 650 K by a chemical solution method.